Pendidikan Multikultural sebagai Perwujudan Profil Pelajar Pancasila melalui Pengajaran Pendidikan Agama Islam dan Budi Pekerti - MARDHIANA ANGGRAINI (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2023)
Abstract : Human diversity has been explicitly mentioned in the Qur'an as sunatullah. Diversity has great potential for Indonesia's progress, but on the other hand it is also vulnerable to social and community conflicts. Therefore, it is necessary to have a basic understanding of living together in different cultures. One of the efforts to realize multiculturalism is multicultural education which is practiced in the Profil Pelajar Pancasila through the teaching of Islamic Religious Education and Character. This article is part of a qualitative study conducted using the library research method. One of the characters that corresponds to multicultural education in the Profil Pelajar Pancasila is global diversity. With global diversity, Indonesian students maintain their noble culture, locality and identity, and are open to interacting with other cultures so as to foster a spirit of mutual respect and the opportunity to form a culture that is noble, positive and does not conflict with the nation's culture. Elements and keys to global diversity include cultural knowledge and appreciation, cross-cultural communication skills in interacting with others, reflection and responsibility for diversity experiences. Islam is a religion of